52nd Aerospace Sciences Meeting 2014
DOI: 10.2514/6.2014-0960
|View full text |Cite
|
Sign up to set email alerts
|

Vortex Control by Non-Equilibrium Plasma

Abstract: Nomenclature PVR= plasma vortex reactor HF = high frequency F HF = HF frequency F M = modulation frequency of HFD T i = pulse duration I = electric discharge current V = electric discharge voltage Q e = power input in plasma V x = axial flow velocity V t = tangential flow velocity P st = static pressure T g = gas temperature T R = rotation temperature T V = vibration temperature T e = electron excitation temperature T b = black body temperature Abstract Study of a longitudinal plasmoid in swirl flow is very im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Compared with other discharge styles, RF discharge exhibits several advantages including high heating efficiency, strong discharge stability, and convenient power adjustment. [15,16] In particular, previous studies also confirmed the favorable thermal effect of RF-DBD. [17] All of these suggest that RF plasma has great potential in shock wave control.…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…Compared with other discharge styles, RF discharge exhibits several advantages including high heating efficiency, strong discharge stability, and convenient power adjustment. [15,16] In particular, previous studies also confirmed the favorable thermal effect of RF-DBD. [17] All of these suggest that RF plasma has great potential in shock wave control.…”
Section: Introductionmentioning
confidence: 55%
“…In addition, the characteristic structure of the vortex cluster can be characterized by both magnitude and size. [15] Hence, it can be concluded that the vortex cluster in the boundary layer expands after the application of actuation.…”
Section: Control Principle Of Oblique Shock Wave Under Rf Discharge P...mentioning
confidence: 98%
“…The second problem was used to calculate flow with M ∼ 0.2 and complex geometry. The results where benchmarked against PIV [9] measurements and gave good correlation with both time-steppers.…”
Section: Benchmarks and Some Resultsmentioning
confidence: 90%
“…One promising plasma actuation type is radio frequency (RF) discharge plasma actuation, in which the applied voltage oscillates at frequencies of up to MHz to sustain the discharge primarily through electron diffusion, as investigated in [4, 5]. Apart from high heating efficiency, the RF discharge has the advantages of high stability in the high‐speed airflow and convenient power regulation, which has wide application prospect in flow control [6–8].…”
Section: Introductionmentioning
confidence: 99%